Myocardial Imaging with Technetium-99m CPI: Initial Experience in the Human - Holman, Leonard B.; Sporn, Victor; Jones, Alun G.; Sia, Benjamin S.T.; Perez-Balino, Nestor; Davison, Alan; Lister-James, John; Kronauge, James F.; Mitta, Aldo Emilio Antonio; Camin, Leopoldo L.; Campbell, Stephen; Williams, Stephen J.; et al. (1987)
Fil: Sporn, Victor Comisión Nacional de Energía Atómica; Argentina